Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3389/fped.2023.1092671
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for neonatal sepsis among neonates in the neonatal intensive care unit at Hawassa University Comprehensive Specialized Hospital and Adare General Hospital in Hawassa City, Ethiopia

Abstract: BackgroundNeonatal sepsis (NS) is a serious blood bacterial infection in children of 28 days or younger, manifested by systemic signs and symptoms of infection. Neonatal sepsis has become one of the leading causes of admission and death in developing countries like Ethiopia. Understanding different risk factors for neonatal sepsis is essential for early diagnosis and treatment. So, this study aimed to assess the risk factors for neonatal sepsis among neonates at Hawassa University Comprehensive Specialized Hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 24 publications
0
1
0
Order By: Relevance
“…In this study, although the proportion of positive cultures was slightly higher in pre-term and male babies compared to full-term and female babies, consistent with the findings of other studies (14,15), this difference was not statistically significant. In our study, we did not find a significant relationship between neutrophil count and infection.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, although the proportion of positive cultures was slightly higher in pre-term and male babies compared to full-term and female babies, consistent with the findings of other studies (14,15), this difference was not statistically significant. In our study, we did not find a significant relationship between neutrophil count and infection.…”
Section: Discussionsupporting
confidence: 90%
“…Neonates who were born to mothers with a history of foul-smelling liquor had greater odds of developing neonatal sepsis, with reference to those born from mothers without a history of foul-smelling liquor. Foul-smelling liquor has similarly been linked with neonatal sepsis in previous studies [ 40 , 41 ] and suggested to an indication of chorioamnionitis which results in systemic infection when neonates come in contact with it. Early detection and treatment of the mother with chorioamnionitis could reduce the baby’s chances of developing neonatal sepsis.…”
Section: Discussionmentioning
confidence: 81%
“…We presented categorical data as both numbers and percentages. Maternal age below 20 years, primigravida mother, and a 5-minute Apgar score below 7 may be associated with EOS according to previous studies [6,[12][13][14][15][16]. Thus, we dichotomized these variables accordingly.…”
Section: Discussionmentioning
confidence: 99%